The comparison of colonization dynamic of vibrio cholerae vaccine candidates in vivo and in vitro - Tanzining, Tanzining (Universiti Sains Malaysia, 2008)
Vibrio cholerae is a Gram-negative bacterial pathogen that can cause cholera. Cholera is characterized by a severe watery diarrhea and it is a life-threatening diarrheal disease that eventually kills the victims within hours of the onset of symptoms if not treated on time. There are many killed and live-attenuated vaccines developed for V. cho/erae, but the efficacy of these vaccines varies and does not give life long protection. However, there is still no commercially available vaccine for 0139 V. cho/erae serogroup, which is the most virulent strain. Thus, in this study, several V. cholerae vaccine candidates which were derivatives of the 0139 Vibrio cholerae serogroup with the mutation on different virulence factors were used to study the cholera pathogenesis. The cytotoxicity assay was carried out to confirm the role of RTX toxin which causes the rounding effect on the HEp-2 cells. SDS-PAGE and Western Blot were carried out to further examine the RTX toxin property in causing depolymerization of actin and cross-linking of actin monomers. VCUSM 9P, VCUSM liP, VCUSM 14P and VCUSM 17P caused rounding of the HEp-2 cells, depolymerization of actin and cross-linking of actin monomers. VCUSM 1 OP which has mutation on both rtx A and C genes showed no effect of the RTX toxin to the HEp-2 cells. In the cholera pathogenesis study, both in vivo and in vitro colonization assays were performed and the colonization efficiency of the bacteria in both methods were compared. The results showed that the colonization of V. cholerae vaccine candidates in the in vitro colonization method is more efficient than the in vivo method.